A framework for evaluating ecohydrological-based liveability in a rapidly urbanising region of Indonesia. Issue 3 (2nd September 2018) - Danielaini, Titih Titisari; Maheshwari, Basant; Hagare, Dharmappa
ABSTRACT: We surveyed households within Cirebon Metropolitan Region (CMR) in Indonesia to assess ecohydrological changes and their impacts on urban and peri-urban liveability. Composite indices were developed based on the subjective assessment of selected liveability indicators representing socio-ecohydrological functions of the region. This study identified five underlying structures of satisfaction factors, viz., personal, residential, neighbourhood, regional, and watershed. The study shows that liveability satisfaction varied depending upon the level of urbanisation in the CMR. The study also indicates that the challenge to improve regional sustainability is significant in the urban–peri-urban transition zone where the poor are more likely to live and are more directly affected by urban expansion and degradation of the local ecosystem. The analytical framework developed in this study can help local and regional government agencies to examine holistic solutions that focus more on place-based needs for long-term liveability and sustainability.